2019
DOI: 10.1111/dmcn.14204
|View full text |Cite
|
Sign up to set email alerts
|

Pain coping strategies in children with cerebral palsy

Abstract: Aim To describe coping strategies in children and adolescents with cerebral palsy (CP), relative to age. Method Patients were prospectively recruited from two paediatric rehabilitation centres in France. The Pediatric Pain Coping Inventory – French and Structured Pain Questionnaire were completed by an experienced professional for each child. Results One hundred and forty‐two children with CP were included (80 males, 62 females; median age 12y; IQR=8–15y). They generally used fewer coping strategies than typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Pain coping strategies by children and adolescents seem to be intuitive and not based on professional support. Many studies have shown coping strategies change with age [27][28][29]. These changes can be explained based on Piaget's theory of cognitive development.…”
Section: Discussionmentioning
confidence: 99%
“…Pain coping strategies by children and adolescents seem to be intuitive and not based on professional support. Many studies have shown coping strategies change with age [27][28][29]. These changes can be explained based on Piaget's theory of cognitive development.…”
Section: Discussionmentioning
confidence: 99%
“…Chaleat‐Valayer et al 18 . demonstrated that children with CP and pain are less likely to use active coping strategies than typically developing children.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that the presence of a significant other (mother) increased pain sensitivity in children with CP. Although children with CP have multiple pain experiences and increased pain sensitivity from an early age [ 24 ], they seem to highly rely on social support and on a low use of other active strategies for coping with this pain [ 6 ], in contrast to healthy peers who use a greater range of adaptative pain-coping strategies. Previous research has shown that perceived social support may regulate physiological stress responses and pain ratings in a healthy population [ 16 , 17 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain negatively affects quality of life [ 2 , 3 ] and participation [ 2 , 4 ]. Furthermore, individuals with CP have altered somatosensory processing and pain sensitivity [ 5 ], requiring the development of specific coping strategies to manage pain [ 6 ].…”
Section: Introductionmentioning
confidence: 99%